Deciphering the system of a systematic review - Jatinder Kaur Dhillon; Namrata C Gill (Wolters Kluwer Medknow Publications, 2014)
All clinical decisions and research essentially begins with the review of pre-existing literature. It helps to make our clinical decisions based on an overview of all the literature concerning the particular clinical problem. This requires a lot of time and effort, which is becoming scarce in this day and age. Literature reviews shorten the time by offering relevant evidence in a concise form. However, narrative reviews might not be objective and unbiased. This drawback is overcome by systematic reviews. There is still some apprehension regarding undertaking systematic reviews due to lack of information. This article is an attempt to explain the concept of systematic reviews and methods used for conducting the same, which will be helpful in day-to- day clinical practice as well as research.